Altered Brain Function Activity in Patients With Dysphagia After Cerebral Infarction: A Resting-State Functional Magnetic Resonance Imaging Study - Li, Lei; Liu, Jiayu; Liang, Fenxiong; Chen, Haidong; Zhan, Rungen; Zhao, Shengli; Li, Tiao; Peng, Yongjun (Frontiers in Neurology, 2022)
Objective: Dysphagia after cerebral infarction (DYS) has been detected in several brain regions through resting-state functional magnetic resonance imaging (rs-fMRI). In this study, we used two rs-fMRI measures to investigate the changes in brain function activity in DYS and their correlations with dysphagia severity. Method: In this study, a total of 22 patients with DYS were compared with 30 patients without dysphagia (non-DYS) matched for baseline characteristics. Then, rs-fMRI scans were performed in both groups,and regional homogeneity (ReHo) and fractional amplitude of low-frequency fluctuation (fALFF) values were calculated in both groups.The two-sample t-test was used to compare ReHo and fALFF between the groups. Pearson’s correlation analysis was used to determine the correlations between the ReHo and fALFF of the abnormal brain regions and the scores of the Functional Oral Intake Scale (FOIS), Standardized Bedside Swallowing Assessment (SSA), Videofluoroscopic Swallowing Study (VFSS) and Penetration-Aspiration Scale (PAS). Results: Compared with the non-DYS group, the DYS group showed decreased ReHo values in the left thalamus, left parietal lobe and right temporal lobe and significantly decreased fALFF values in the right middle temporal gyrus and inferior parietal lobule. In the DYS group, the ReHo of the right temporal lobe was positively correlated with SSA score and PAS score (r=0.704, p＜0.001 and r=0.707, p＜0.001, respectively) but negatively correlated with VFSS score (r=-0.741, p＜0.001). The ReHo of the left parietal lobe was positively correlated with SSA and PAS (r=0.621,p=0.002 and r=0.682, p＜0.001, respectively) but negatively correlated with VFSS (r=-0.679,p=0.001). Conclusion: Changes in the brain function activity of these regions are related to dysphagia severity. The DYS group with high ReHo values in the right temporal and left parietal lobes had severe dysphagia.